Uncovering the effects of copper feed supplementation on the selection of copper-tolerant and antibiotic-resistant Enterococcus in poultry production for sustainable environmental practices - Rebelo, Andreia (2023)
The use of antibiotics in animal production is linked to the emergence and spread of antibiotic-resistant bacteria, a threat to animal, environmental and human health. Copper (Cu) is an essential element in poultry diets and an alternative to antibiotics, supplementing inorganic or organic trace mineral feeds (ITMF/OTMF). However, its contribution to select multidrug-resistant (MDR) and Cu tolerant Enterococcus, a bacteria with a human-animal-environment-food interface, remains uncertain. We evaluated whether feeding chickens with Cu-ITMF or Cu-OTMF contributes to the selection of Cu tolerant and MDR Enterococcus from rearing to slaughter. Animal faeces [2–3-days-old (n = 18); pre-slaughter (n = 16)] and their meat (n = 18), drinking-water (n = 14) and feed (n = 18) from seven intensive farms with ITMF and OTMF flocks (10.000–64.000 animals each; 2019–2020; Portugal) were sampled. Enterococcus were studied by cultural, molecular and whole-genome sequencing methods and Cu concentrations by ICP-MS. Enterococcus (n = 477; 60 % MDR) were identified in 80 % of the samples, with >50 % carrying isolates resistant to tetracycline, quinupristin-dalfopristin, erythromycin, streptomycin, ampicillin or ciprofloxacin. Enterococcus with Cu tolerance genes, especially tcrB ± cueO, were mainly found in faeces (85 %; E. faecium/E. lactis) of ITMF/OTMF flocks. Similar occurrence and load of tcrB ± cueO Enterococcus in the faeces was detected throughout the chickens' lifespan in the ITMF/OTMF flocks, decreasing in meat. Most of the polyclonal MDR Enterococcus population carrying tcrB ± cueO or only cueO (67 %) showed a wild-type phenotype (MICCuSO4 ≤ 12 mM) linked to absence of tcrYAZB or truncated variants, also detected in 85 % of Enterococcus public genomes from poultry. Finally, < 65 μg/g Cu was found in all faecal and meat samples. In conclusion, Cu present in ITMF/OTMF is not selecting Cu tolerant and MDR Enterococcus during chickens' lifespan. However, more studies are needed to assess the minimum concentration of Cu required for MDR bacterial selection and horizontal transfer of antibiotic resistance genes, which would support sustainable practices mitigating antibiotic resistance spread in animal production and the environment beyond.